Acruliopsis gen. n. aus der Ostpaläarktis (Coleoptera, Staphylinidae, Omaliinae, Omaliini) (Beiträge zur Kenntnis ostpaläarktischer Insekten; 14). - Zerche, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 2003)
The genus Acruliopsis gen. n. (type species: Acruliopsis watanabei sp. n.) is described, based on a phylogenetic analysis. Acruliopsis ussuriensis sp. n. (Russia: Primorskiy Kray) and Acruliopsis watanabei sp. n. (Japan: Honshû, Yamanashi-ken) are described and compared with the related species. Acruliopsis denticollis (Sharp, 1889) comb. n. and Acruliopsis nipponica (Watanabe, 1980) comb. n. are transferred from the genus Pycnoglypta Thomson, 1858. A key to species is provided. Keywords Coleoptera, Staphylinidae, Omaliinae, Omaliini, new genus, new species, redescriptions, phylogeny, key, Far East of Russia, Japan. Nomenclatural Acts denticollis (Sharp, 1889) (Acruliopsis), comb. n. hitherto Omalium denticolle nipponica (Watanabe, 1980) (Acruliopsis), comb. n. hitherto Pycnoglypta nipponica ussuriensis Zerche, 2003 (Acruliopsis), spec. n. watanabei Zerche, 2003 (Acruliopsis), spec. n. Acruliopsis Zerche, 2003 (Staphylinidae), gen. n.